2017
DOI: 10.1038/s41598-017-08711-6
|View full text |Cite
|
Sign up to set email alerts
|

Mitigation of sepsis-induced inflammatory responses and organ injury through targeting Wnt/β-catenin signaling

Abstract: The Wnt/β-catenin pathway has been involved in regulating inflammation in various infectious and inflammatory diseases. Sepsis is a life-threatening condition caused by dysregulated inflammatory response to infection with no effective therapy available. Recently elevated Wnt/β-catenin signaling has been detected in sepsis. However, its contribution to sepsis-associated inflammatory response remains to be explored. In this study, we show that inhibition of Wnt/β-catenin signaling reduces inflammation and mitiga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
42
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(45 citation statements)
references
References 58 publications
3
42
0
Order By: Relevance
“…Since Wnt/b-catenin signaling is a major pathway involving in renal fibrosis, and Sirt6 has been reported to control Wnt signaling in hematopoietic stem cell homeostasis, 28,32 b-catenin-responsive transcription inhibitor, iCRT3. 33 We first confirmed the effect of iCRT3 on b-catenin activity by glucose induction. 35,36 It is unclear whether Sirt6 might act as a deacetylase for b-catenin in the context of fibrogenesis.…”
Section: Sirt6 Negatively Regulates B-catenin Signaling Pathwaysupporting
confidence: 58%
“…Since Wnt/b-catenin signaling is a major pathway involving in renal fibrosis, and Sirt6 has been reported to control Wnt signaling in hematopoietic stem cell homeostasis, 28,32 b-catenin-responsive transcription inhibitor, iCRT3. 33 We first confirmed the effect of iCRT3 on b-catenin activity by glucose induction. 35,36 It is unclear whether Sirt6 might act as a deacetylase for b-catenin in the context of fibrogenesis.…”
Section: Sirt6 Negatively Regulates B-catenin Signaling Pathwaysupporting
confidence: 58%
“…[ 36,37 ] A report showed that suppression of Wnt/β‐catenin could abate inflammation, meanwhile assuage sepsis‐engendered organ damage. [ 38 ] On the other hand, Chen et al [ 32 ] and Huang et al [ 39 ] have revealed that lncRNA NEAT1 and PVT1 affected LPS‐triggered septic AKI through regulation of the NF‐κB pathway. In our research, we also want to confirm whether Wnt/β‐catenin and NF‐κB signaling influences the protection of HOXA‐AS2 in sepsis‐triggered AKI.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, disruption of the pyridine cross-linking formation affects collagen synthesis of ECM and decreases fibrotic lesions. It was previously discovered that iCRT3 blocks signaling transduction of Wnt/β-catenin and TGFβ1/Smad3 [14,15], thus inhibiting downstream lysyl hydroxylase 3 gene and protein expression. It was postulated that iCRT3 might possess anti-fibrotic properties by reducing the total number of lysine pyridinoline cross-links and hydroxyallysine pyridinoline cross-linking formation.…”
Section: Discussionmentioning
confidence: 99%
“…iCRT3 is a small molecule inhibitor of the Wnt/β-catenin signaling pathway. Its inhibition is achieved through blocking β-catenin nuclear transfer, inhibiting Wnt/β-catenin signaling transduction [14,15]. TGF-β acts as a key factor whose activation has been implicated in both pulmonary fibrosis (PF) and airway remodeling in this process [16].…”
Section: Introductionmentioning
confidence: 99%